Principles of healing of virus-infected raspberry varieties by chemotherapy in vitro - Medvedeva, T.; Natalchuk, T.; Suprun, K.; Ryaba, I.; Triapitsyna, N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
Most of promising raspberry varieties need to be heal from complex viral infections. Development of the most standardized and universal plant healing methods — one of the actual tasks of biotechnology works for raspberries plant material production. The decrease of virus concentration in explants of some promising hybrid forms and varieties of raspberry affected by complex viral infection were analyzed with semi quantitative LIA method after explants treatment with ribavirin. Rated the therapeutic, toxic and prolonged effect of ribavirin for elimination of four viruses were evaluated. It was revealed universal peculiarities for chemotherapy of raspberries shoots using this virocide.